Adolescents and young adults infected by the Human Papillomavirus (HPV): vulnerabilities and feelings experienced - Maria Carolina Oliveira Reis; Adenilda Lima Lopes Martins; Rosely Cabral de Carvalho; Rita de Cássia Rocha Moreira; Marcelo Torres Peixoto; Sandra Ely Barbosa de Souza (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To know the vulnerabilities experienced by adolescents and young adults infected by the Human Papillomavirus attended at a reference center in Feira de Santana - Bahia. Method: Qualitative study, carried out with a semi-structured interview with 20 adolescents and young adults, from November 2020 to February 2021. For data analysis, the Content Analysis proposed by Bardin and the software Iramuteq were used. Results: The discovery of the infection highlights the misunderstanding about illness, fear, despair and guilt, individual and collective dimensions that point to little knowledge about the Human Papillomavirus. Final considerations: It is necessary to implement public policies to minimize risks, through knowledge and confrontation of sexually transmitted infections, as well as health promotion strategies and shared decisions for the process of behavior change in adolescents and young adults.